A review on ethnobotany, phytochemistry, and pharmacology of Microdesmis keayana and Microdesmis puberula (Pandaceae) - Uchenna Benjamin Okeke, Onome Mary Adeboye, Funmilayo Racheal Adeniyi, Emmanuel Ayodeji Agbebi (Journal of Applied Pharmaceutical Science, 2023)
Microdesmis keayana and Microdesmis puberula (Pandaceae) are two major plant species in the genus Microdesmis. They are dioecious shrubs, very similar in their morphology, botanical distribution, and medicinal uses, and native to most tropical and subtropical African regions. Traditionally, they are commonly used to treat erectile dysfunction, general body pain, snake bites, skin and intestinal infections, tumors, diarrhea, diabetes, obesity, headache, and migraine. This review is aimed to provide a compendium of ethnopharmacological and phytochemical information on the Microdesmis plants for future research and drug development initiatives. Relevant books and electronic databases were sourced during the literature review. Several phytochemical investigations resulted in the isolation and identification of about eight compounds from M. keayana and M. puberula, including four spermines and five spermidine alkaloids, and a quinoline, which were all isolated from the methanol and hydromethanolic root extracts of the two plants. In vivo and in vitro pharmacological studies of the plants showed aphrodisiac, antimalarial, antimicrobial, antioxidant, analgesic, antistress, and antisickling activities, which gave credence to their use in ethnomedicine. The plants can potentially be used for several disease conditions, including erectile dysfunction, malaria, infections, and pains, with a view to isolating bioactive lead compounds for drug development.
Keywords: Microdesmis, aphrodisiac, phytochemistry, ethnomedicine, spermine, spermidine